بعثتِ نبوی سے قبل عرب معاشرت اور قبائلی نظام: مذہبی، سماجی، سیاسی، معاشی اور اخلاقی اثرات کا تجزیاتی مطالعہ: This version adds more fluidity to the title while keeping the focus on the analytical study of the key aspects of pre-Islamic Arab society and the tribal system. - Aysha Saeed; Dr. Naeem Qaiser Al-Azhari; Rubab fatma (International Research Journal of Arabic and Islamic Studies, 2024)
Before the advent of Prophet Muhammad (PBUH), pre-Islamic Arab society was structured around a tribal system, where each tribe functioned as an autonomous entity with its own leader and a strong sense of internal collectivism. The honor and dignity of tribe members were fiercely protected, yet women were marginalized and practices such as female infanticide were common. Economically, Arabs engaged in trade, agriculture, and herding, with Mecca serving as a crucial commercial hub. Religiously, the society was polytheistic, with numerous idols worshipped in the Kaaba and each tribe revering its own deities. Although hospitality, bravery, and loyalty were esteemed values, the society also experienced moral shortcomings including widespread deceit and oppression. The arrival of Prophet Muhammad (PBUH) marked a profound shift, challenging the existing social, economic, and religious norms. His teachings introduced monotheism, justice, and equality, fundamentally transforming Arab society. This paper provides a comprehensive analysis of the tribal system's impact on various aspects of pre-Islamic Arab life, laying the groundwork for understanding the significant reforms brought about by Islam.